Assessment of Immuno-histochemical Expression of CD44 in Renal Tumors - Banan Mohammed; khalid Abdulfattah Khattab; Payman Salim (Al-Anbar Medical Journal)
Background: Cluster of differentiation 44 (CD44) is the most commonly reported immune marker of the cancer stem cells in renal cell carcinoma.Objectives: To assess the frequency of CD44 expression in renal tumors, to assess the expression of CD44 in different histological types, and to detect its association with variable clinicopathological parameters.Materials and methods: In this retrospective case series study, 76 cases of primary renal tumors were obtained by nephrectomy, and a study of CD44 was done by using the immunohistochemical technique.Results: The age of the patients ranged from 29-82 years with a mean of 54.8 ±11.96 with a male to female ratio of 1.05:1. Tumor size ranged from 2-17 cm with a mean of 6.2 ±3.23. Clear cell renal cell carcinoma was forming 61.83% of the cases. Among all cases, a positive CD44 expression was observed in 35 (46.05%) cases; among the malignant cases, CD44 was positive in 32 (45.71%). CD44 immunohistochemical stain showed significantly higher expression in cases with higher nuclear grade and tumor stage (P-value of 0.0376 and 0.0075, respectively). CD44 cannot differentiate between benign and malignant renal tumors.Conclusion: CD44 immune marker can be used as a prognostic factor to predict the aggressive behavior of renal tumors. It can also be used with standard prognostic markers to add prognostic information for subgrouping cases within the same grade and stage.